Social Support and Occupational Engagement Among Korean Undergraduates: The Moderating and Mediating Effect of Work Volition. (June 2018) - Kim, Na-Rae; Kim, Haram J.; Lee, Ki-Hak
Career paths are no longer linear or predictable due to the instability and dynamic changes occurring in the work environment. Career researchers have acknowledged this trend and emphasized the significance of individuals' actual behaviors in career development. Occupational engagement is an essential behavior that leads to successful and satisfactory career development in college students. The current study examined the mediating and moderating roles of work volition in the relationship between social support and occupational engagement. A total of 233 (80 males, 153 females) Korean undergraduates participated in the survey. The results were as follows: Work volition partially mediated the positive relationship between social support and occupational engagement. That is, people who felt they had higher social support reported more work volition, which in turn resulted in more active participation in occupational engagement. Also, the moderation effect of work volition was found between social support and occupational engagement. Thus, the influence of social support on occupational engagement was greater for those with an average or above level of work volition. The results showed that environmental social support and individual work volition are vital factors in improving occupational engagement. The implications and suggestions for practical uses and future research were suggested.